Fifty shades of QE: Comparing findings of central bankers and academics - Brian Fabo; Martina Jancoková; Elisabeth Kempf; Ľuboš Pástor (European Central Bank (ECB), 2021)
We compare the findings of central bank researchers and academic economists regarding the macroeconomic effects of quantitative easing (QE). We find that central bank papers find QE to be more effective than academic papers do. Central bank papers report larger effects of QE on output and in ation. They also report QE effects on output that are more significant, both statistically and economically, and they use more positive language in the abstract. Central bank researchers who report larger QE effects on output experience more favorable career outcomes. A survey of central banks reveals substantial involvement of bank management in research production.
Keywords: A11; E52; E58; G28; 330; economic research; quantitative easing; QE; central bank; career concerns